PENGARUH PERAN PERANGKAT DESA, KEBIJAKAN DESA, AKSESIBILITAS LAPORAN KEUANGAN, DAN SISKEUDES TERHADAP AKUNTABILITAS DESA DI KECAMATAN PEMALANG - Ali Imron (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2023)
ABSTRACT : This study used purposive sampling of 52 respondents. The testing in this study was carried out by testing the validity, reliability, classical assumptions, testing the hypothesis in the form of a t test, multiple linear regression analysis, the coefficient of determination. The results of the validity test for each variable question item are valid because the value of rtable > rcount. The results of the reliability test on each variable question item are reliable because the Cronbach alpha value is > 0.6. The results of multiple linear regression analysis in this study showed the variable Role of Village Officials (X1), Village Policy variables (X2), Financial Report Accessibility variables (X3). The SISKEUDES variable (X4) has an effect on Village Financial Accountability.